2022
DOI: 10.1186/s13098-022-00793-1
|View full text |Cite
|
Sign up to set email alerts
|

25-hydroxyvitamin D levels are inversely related to metabolic syndrome risk profile in northern Chinese subjects without vitamin D supplementation

Abstract: Background The comparatively low 25 hydroxyvitamin D [25(OH)D] levels have been reported in patients with metabolic syndrome (MetS). Herein we investigated the cross-sectional and longitudinal relationships between serum 25(OH)D levels and MetS risk profile in northern middle-aged Chinese subjects without vitamin D supplementation. Methods A cohort of 211 participants including 151 MetS patients and 60 controls at 20–69 years of age were enrolled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Several studies have shown most of the mean values of MetS components (waist circumference, SBP, DBP, fasting glucose and TGs) to be significantly higher in people with MetS compared to the control group, while mean values of HDL-c concentrations were significantly lower compared to the group without MetS [ 35 , 36 , 37 ]. Guembe et al [ 36 ] concluded from their study that MetS was independently associated with CVD risk and with mortality associated with both cardiovascular and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown most of the mean values of MetS components (waist circumference, SBP, DBP, fasting glucose and TGs) to be significantly higher in people with MetS compared to the control group, while mean values of HDL-c concentrations were significantly lower compared to the group without MetS [ 35 , 36 , 37 ]. Guembe et al [ 36 ] concluded from their study that MetS was independently associated with CVD risk and with mortality associated with both cardiovascular and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%